If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 4) + 5(3x + -5) = 3(x + -7) + 8 Reorder the terms: 2(4 + 3x) + 5(3x + -5) = 3(x + -7) + 8 (4 * 2 + 3x * 2) + 5(3x + -5) = 3(x + -7) + 8 (8 + 6x) + 5(3x + -5) = 3(x + -7) + 8 Reorder the terms: 8 + 6x + 5(-5 + 3x) = 3(x + -7) + 8 8 + 6x + (-5 * 5 + 3x * 5) = 3(x + -7) + 8 8 + 6x + (-25 + 15x) = 3(x + -7) + 8 Reorder the terms: 8 + -25 + 6x + 15x = 3(x + -7) + 8 Combine like terms: 8 + -25 = -17 -17 + 6x + 15x = 3(x + -7) + 8 Combine like terms: 6x + 15x = 21x -17 + 21x = 3(x + -7) + 8 Reorder the terms: -17 + 21x = 3(-7 + x) + 8 -17 + 21x = (-7 * 3 + x * 3) + 8 -17 + 21x = (-21 + 3x) + 8 Reorder the terms: -17 + 21x = -21 + 8 + 3x Combine like terms: -21 + 8 = -13 -17 + 21x = -13 + 3x Solving -17 + 21x = -13 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -17 + 21x + -3x = -13 + 3x + -3x Combine like terms: 21x + -3x = 18x -17 + 18x = -13 + 3x + -3x Combine like terms: 3x + -3x = 0 -17 + 18x = -13 + 0 -17 + 18x = -13 Add '17' to each side of the equation. -17 + 17 + 18x = -13 + 17 Combine like terms: -17 + 17 = 0 0 + 18x = -13 + 17 18x = -13 + 17 Combine like terms: -13 + 17 = 4 18x = 4 Divide each side by '18'. x = 0.2222222222 Simplifying x = 0.2222222222
| 3x+2=2x+x-1 | | 7x(2x+3)=56 | | p^2+x^2y^2q^2=x^2z^2 | | 5=6p | | 6+2x-1=9x+7-6x | | 3d+5+17= | | x(y+2)+y=1 | | 2(3x-1)=3x-2 | | x-x*0.1=500 | | 9y-9y^2-2=0 | | t-1.5=5 | | 7(x-1)-(x-4)=8x-1 | | 4+1/4+0.75=x | | (2x+9)+(-3x+9)= | | 25x^3-4x^2-150x+150=0 | | 5x+7-3x-2=4x-1 | | 5x*7-3x-2=4x-1 | | 8x^2+14x-5=0 | | X-(360-x)=124 | | 48=9W-W | | X+10.4=12.2 | | H-18=11 | | 6x+36=3x+76 | | z^2+(z+3)i+1=0 | | e^3-5x=531 | | 2x^3+3x^2+20=0 | | (m-5)(5m+3)=0 | | X^2-10x-3=-12 | | ln(y)=2x+5 | | (5x-3)+log(4)*(9-x)=3 | | (16x^2+36)= | | v=-3i |